Studi Implementasi Metode Demonstrasi Guna Peningkatan Kompetensi Lompat Jauh pada Siswa Kelas IV Sekolah Dasar Negeri Bulusari I Kabupaten Kediri Tahun Pelajaran 2024/2025 - Moch. Miftachurrohman; Wasis Himawanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Physical Education, Sports, and Health (PJOK) plays an important role in developing students' physical, psychological, motoric, cognitive, and affective abilities, with one of the materials being the long jump which involves the stages of starting, pushing, floating, and landing. A classroom action research (CAR) at SDN Bulusari I, Tarokan District, Kediri, aims to determine the application of the demonstration method in long jump learning for fourth grade students, as well as the extent to which their abilities and understanding have increased. By using the spiral model, this study shows that the application of the demonstration method has succeeded in increasing the effectiveness of learning, as evidenced by the increase in the percentage of research results from 84% in cycle I to 87% in cycle II, which indicates that the learning process is going well and students' understanding of the long jump material has increased.